The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/phn.12635
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the intention to use adult preventive health services in Taiwan

Abstract: Objective: This research aimed to examine the factors associated with the intention to use adult preventive health services in Taiwan. Design and Sample:Using Andersen's behavioral model, we employed a cross-sectional descriptive design to investigate 500 samples from four communities in southern Taiwan. Measures:We used a self-reported survey to assess participants' intention to use adult preventive health services, and the predisposing, enabling, and need factors influencing their intention.Results: Intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…This reflects that the working adult group with the intent to purchase health insurance may be influenced to actually purchase a health insurance plan. Apart from being in agreement with the TPB, the outcomes are also in line with that reported by Hsieh et al (2019), Berkman et al (2011), and Prabawanti et al (2014), who found that consumer intention reflects the actual purchase behavioral adoption. Additionally, the mediating effect of intention to purchase health insurance on the relationships of health insurance, perceived usefulness, attitude toward health insurance, subjective norm, and perceived behavioral control with purchase of health insurance had been statistically significant.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This reflects that the working adult group with the intent to purchase health insurance may be influenced to actually purchase a health insurance plan. Apart from being in agreement with the TPB, the outcomes are also in line with that reported by Hsieh et al (2019), Berkman et al (2011), and Prabawanti et al (2014), who found that consumer intention reflects the actual purchase behavioral adoption. Additionally, the mediating effect of intention to purchase health insurance on the relationships of health insurance, perceived usefulness, attitude toward health insurance, subjective norm, and perceived behavioral control with purchase of health insurance had been statistically significant.…”
Section: Discussionsupporting
confidence: 88%
“…Past studies (De Cannière et al, 2009; Wang & Hazen, 2016; Weedige et al, 2019) reported a positive correlation between intention and purchase behavior. Nursiana et al (2021), and Hsieh et al (2019) discovered that the intention to use adult preventive health services was more significantly explained by several enabling factors. In the context of health insurance, adult working consumers reckon that behavioral intentions may affect their actual behavior of purchasing healthcare insurance products or services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the results, enabling factors were the best predictors of vaccine intention and subsequent uptake. Similar findings have recently been reported by Hsieh et al; the enabling factor was counted as one factor associated with using adult preventive health services [ 43 ]. Duval et al's study indicated that several modifiable factors, including knowledge, perceived self-efficacy, and societal and colleagues' support, were associated with willingness to recommend vaccines [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the elderly without chronic diseases, the elderly with chronic diseases used more preventive health services (β = 0.397, P < 0.05). With the decline of health status, the elderly with chronic diseases have a stronger demand for prevention and health care, which is consistent with the research of Li [ 11 ]. The disease is a major adverse factor that perplexes the elderly in their later years, and the elderly diseases are mainly cardiovascular and cerebrovascular diseases (hypertension, coronary heart disease, and cerebral apoplexy), diabetes, and other common chronic diseases.…”
Section: Resultssupporting
confidence: 84%
“…The government should further improve the classification of the elderly’s health status and economic income evaluation mechanism, formulate detailed and reasonable service subsidy standards, and provide appropriate subsidies for the purchase of health and elderly services for low-income elderly people who do have a demand for health and elderly care services and lack financial capacity. By doing this, service provision organizations can transform potential demands into actual demands and increase service utilization rate [ 11 ]. At the same time, differentiated government subsidies and the scope of government-purchased services can be established according to different types and levels of health and elderly care services, and the threshold for enjoying government-purchased services can be appropriately relaxed, so that more needy elderly people can enjoy free services.…”
Section: Discussionmentioning
confidence: 99%